Papua New Guinea : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Papua New Guinea (PNG) is facing strong headwinds from lower global commodity prices. Although the commencement of liquefied natural gas (LNG) production has boosted overall GDP growth in 2014-15, the slow growth of the nonresource sector calls for a renewed policy focus on inclusive growth in the post-LNG construction period. Risks to the outlook are increasingly skewed to the downside. Fiscal consolidation necessitated by weaker-than-anticipated revenue performance will dampen nonresource growth over the short run, and a weak global economy could further dampen external demand and commodity prices.